2013
DOI: 10.1128/jvi.01950-12
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the St. Louis Encephalitis Virus Postfusion Envelope Trimer

Abstract: St. Louis encephalitis virus (SLEV) is a mosquito-borne flavivirus responsible for several human encephalitis outbreaks over the last 80 years. Mature flavivirus virions are coated with dimeric envelope (E) proteins that mediate attachment and fusion with host cells. E is a class II fusion protein, the hallmark of which is a distinct dimer-to-trimer rearrangement that occurs upon endosomal acidification and insertion of hydrophobic fusion peptides into the endosomal membrane. Herein, we report the crystal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…However the unaffected fusion activity of the R902A in our functional assay suggests that it is not mandatory for fusion activity (S4B Fig). Indeed it was suggested before that there is no preferred distance between fusion loops of class II proteins required for fusion activity [49]. Finally, it was postulated that histidine residues function as pH sensors in class II membrane fusion proteins from flaviviruses [5053].…”
Section: Resultsmentioning
confidence: 99%
“…However the unaffected fusion activity of the R902A in our functional assay suggests that it is not mandatory for fusion activity (S4B Fig). Indeed it was suggested before that there is no preferred distance between fusion loops of class II proteins required for fusion activity [49]. Finally, it was postulated that histidine residues function as pH sensors in class II membrane fusion proteins from flaviviruses [5053].…”
Section: Resultsmentioning
confidence: 99%
“…These E structures differ not only by oligomeric status, but also display changes in relative conformations and angles among the three E protein domains. Similar E protein structures at various stages of virus development and infection have also been solved for related flaviviruses, such as tick-borne encephalitis virus, yellow fever virus, West Nile virus, Japanese encephalitis virus, and St. Louis encephalitis virus (8,(18)(19)(20)(21)(22)(23)(24).Although the many structures of DENV E protein provide static images of the protein at various stages of infectivity, the key functional residues that mediate the dynamic fusion process Significance Dengue virus (DENV) infects nearly 400 million people annually, and approximately 40% of the world's population lives at risk for infection. Without a therapeutic or vaccine available, DENV remains a major public health burden.…”
mentioning
confidence: 84%
“…These E structures differ not only by oligomeric status, but also display changes in relative conformations and angles among the three E protein domains. Similar E protein structures at various stages of virus development and infection have also been solved for related flaviviruses, such as tick-borne encephalitis virus, yellow fever virus, West Nile virus, Japanese encephalitis virus, and St. Louis encephalitis virus (8,(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 86%
“…Molecular dynamics simulations at low pH have suggested that trimeric, stemless sE might adopt this open conformation (24). Indeed, a recent stemless flavivirus crystal structure reveals splayed fusion loops at an intermediate distance, 17 Å, from the 3-fold axis, 5 Å farther than in the closed conformation (25). It has also been proposed that during the final stages of fusion, the H1 segment of the stem would squeeze between adjacent domains II, maintaining the splayed conformation (7).…”
Section: Dengue Virus Envelope Trimer With Proximal Stemmentioning
confidence: 99%